Numerical investigation of the effects of temporal variations in basal lubrication on englacial strain-rate distribution - Sugiyama, Shin; Gudmundsson, Hilmar; Helbing, Jakob (Annals of Glaciology, 2003)
The effects of spatial and temporal variations in basal lubrication on the englacial strain rate and surface velocity distribution are investigated with a numerical ice-flow model. General aspects of the solutions are compared to measurements made on Lauteraargletscher, Switzerland, in 2001, that showed diurnal fluctuations in both surface velocity and englacial vertical strain. We find that spatial gradients in basal lubrication can set up variations in the deviatoric stress field that increases with distance to the bed and has a maximum value near the glacier surface. This stress field produces a significant strain rate near the surface. The temporal evolution of a slippery zone is identified as a possible cause of the observed diurnal variations in the vertical strain rate. Although general aspects of the measurements can be explained in this way, the calculated vertical strain rates are too small, suggesting that the modeled effective viscosity values using Glen’s flow law are too large near the surface.